POOR SLEEP HYGIENE BEHAVIORS AND SLEEP QUALITY AMONG MEDICAL STUDENTS: A BASNEF MODEL-BASED ANALYSIS AT A MEDICAL UNIVERSITY IN VIETNAM, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe sleep quality among students at Hanoi Medical University using the PSQI and to analyze the association between BASNEF model components and sleep quality.Subjects and methods: A cross-sectional study was conducted on 60 medical students from first to sixth year at Hanoi Medical University in April 2025. Data were collected an online questionnaire including socio-demographic and academic characteristics, BASNEF constructs (beliefs, attitudes, subjective norms, enabling factors, and behaviors), and the PSQI scale. Descriptive statistics and group comparisons were performed.Results: A total of 75% of participants had poor sleep quality (PSQI ≥ 5). All BASNEF components were associated with sleep quality, with attitudes and enabling factors showing the strongest relationships. Students with positive attitudes and better enabling conditions had a higher proportion of good sleep quality. Socio-demographic and academic factors showed some trends but no clear associations.Conclusion: Poor sleep quality is highly prevalent among medical students. BASNEF components, particularly attitudes and enabling factors, play a significant role in sleep quality. Health education interventions should focus on improving attitudes and strengthening enabling conditions to promote healthy sleep behaviors.
Keywords: Sleep quality, sleep hygiene, medical students, BASNEF, PSQI.